Electrocatalytic Hydrogen Evolution Reaction Related to Nanochannel Materials. Issue 10 (1st September 2021) - Pan, Jing; Yu, Shanwu; Jing, Zhangwei; Zhou, Qitao; Dong, Yifan; Lou, Xiaoding; Xia, Fan
Abstract : Due to the high efficiency and clean process, electrocatalytic hydrogen evolution reaction (HER) is emerging as the most promising way for hydrogen (H2 ) production, where the bottleneck is the relatively low catalytic activity for nonprecious electrocatalysts/electrodes. Currently, porous materials with channel structures show great potential toward outstanding HER performance. Herein, existing HER electrocatalysts/electrodes with 1D, 2D, and 3D channels are introduced. Recent advances as well as challenges for HER electrocatalysts/electrodes are presented first. Then, different configuration types comprising electrocatalysts confined in inactive host porous materials, electrocatalysts directly working as host materials, and electrocatalysts confined in active host porous materials are illustrated for 1D, 2D, and 3D, respectively. Finally, the perspective for porous electrocatalysts/electrodes is discussed for future innovations of HER application. Abstract : Herein, recent advances of porous hydrogen evolution reaction (HER) electrocatalysts/electrodes with 1D, 2D, and 3D channels are introduced. The HER performances and fabrication methods related to all kinds of channels are discussed based on the activity of the host materials and the present of the confined materials. Finally, some challenges and perspectives are mentioned.